Stabilization Of Excavated Soil Using Lime (CaCO3) As Fill Material On The Serang - Panimbang Section III Highway - Muhammad F. Dika; Trihanyndio Rendy Satrya; Ria Asih Aryani Soemitro (International Journal Labs, 2025)
The construction of the Serang – Panimbang Toll Road Section III faces the challenge of surplus excavated material dominated by clay shale from the Bojong Formation. This material is categorized as highly plastic clay (CH) with high swelling and shrinkage potential, so it does not meet the specifications as fill material without special treatment. This study aims to evaluate the effectiveness of stabilizing the excavated soil using calcium carbonate (CaCO3)-based lime. The research method was conducted experimentally in the laboratory with variations in lime content additions of 6%, 7%, and 8% to the dry weight of the soil. The tests included physical properties (Atterberg Limits, Specific Gravity) and mechanical properties (Standard Proctor, CBR Soaked, Unconfined Compressive Strength/UCS, and Swelling). The results showed that the original soil had a Plasticity Index (PI) of 61.17% and a very high swelling potential of 6.92%. Stabilization with CaCO3 proved to be effective in improving soil characteristics. The most optimal decrease in PI occurred at a variation of 7% (to 47.63%), but the best improvement in mechanical properties was achieved at a variation of 6%. At a 6% concentration, the soaked CBR value increased from 0.498% to 1.549%, the unconfined compressive strength (qu) increased to 2.681 kg/cm², and the swelling potential decreased dramatically to 1.26%. Thus, a 6% addition concentration is recommended as the optimum variation for soil stabilization at the study site.